Diplodia Tip Blight on Its Way to the North: Drivers of Disease Emergence in Northern Europe - Brodde, Laura; Adamson, Kalev; Julio Camarero, J.; Castaño, Carles; Drenkhan, Rein; Lehtijärvi, Asko; Luchi, Nicola; Migliorini, Duccio; Sánchez-Miranda, Ángela; Stenlid, Jan; Özdağ, Şule; Oliva, Jonàs (Frontiers in Plant Science, 2019)
Disease emergence in northern and boreal forests has been mostly due to tree-pathogen encounters lacking a co-evolutionary past. However, outbreaks involving novel interactions of the host or the pathogen with the environment have been less well documented. Following an increase of records in Northern Europe, the first large outbreak of Diplodia pinea was discovered in Sweden in 2016. By reconstructing the development of the epidemic, we found that disease started ca. 10 years back from several isolated trees in the stand, and ended up affecting almost 90% of the trees in 2016. Limited damage was observed in other plantations in the surroundings of the affected stand, pointing to a new introduced pathogen as the cause of the outbreak. Nevertheless, no genetic differences based on SSR markers were found between isolates of the outbreak area and other Swedish isolates predating the outbreak, nor from other populations in Europe and Asia Minor. On a temporal scale, we saw that warm May and June were associated with higher damage and low tree growth, while cold and rainy conditions seemed to favour growth and deter disease. At a spatial scale, we saw that spread occurred predominantly in the SW aspect-area of the stand. Within that area and based on tree-ring and isotope (δ13C) analyses, we saw that disease occurred on trees that over the years had shown a lower water-use efficiency (WUE). Spore traps showed that highly infected trees were those producing the largest amount of inoculum. D. pinea impaired latewood growth and reduced C reserves in needles and branches proximal to the damaged area. D. pinea attacks can cause serious economic damage by killing new shoots, disrupting the crown and affecting the quality of stems. Our results show that D. pinea has no limitations in becoming a serious pathogen in Northern Europe. Management should focus on reducing inoculum, especially since climate change is making climatic conditions increasingly favourable for this pathogen. We speculate that D. pinea was introduced in the stand via infected planting material. Seedlings should be carefully inspected as D. pinea may be present in a latent stage in asymptomatic tissues.